Contentious performances - Tilly, Charles (Cambridge University Press, 2008)
How can we get inside popular collective struggles and explain how they work? Contentious Performances presents a distinctive approach to analyzing such struggles, drawing especially on incomparably rich evidence from Great Britain between 1758 and 1834. The book accomplishes three main things. First, it presents a logic and method for describing contentious events, occasions on which people publicly make consequential claims on each other. Second, it shows how that logic yields superior explanations of the dynamics in such events, both individually and in the aggregate. Third, it illustrates its methods and arguments by means of detailed analyses of contentious events in Great Britain from 1758 to 1834.